2003
DOI: 10.1136/oem.60.9.699
|View full text |Cite
|
Sign up to set email alerts
|

Do junior doctors take sick leave?: Table 1

Abstract: Nosocomial infections place a heavy burden on overstretched health services. An audit of junior doctors’ sick leave behaviour was undertaken in 1993 and again in 2001. The object was to ascertain the level of common infectious illness and to investigate whether junior doctors were remaining at work inappropriately. The doctors were asked if any factors had influenced their decision to take sick leave or not. Between the two audits several initiatives have been introduced to improve the working conditions of ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 7 publications
(2 reference statements)
3
18
0
Order By: Relevance
“…A total of 8% of the respondents in our survey reported that their programme required documentation of reasons for time‐off requests. Previous studies suggest that residents are less likely to access health care (physical or mental) because of concerns over confidentiality and privacy 23,24 . Thus, any requirement that residents document why they are requesting time off is likely to deter them from addressing important needs such as mental health appointments.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 8% of the respondents in our survey reported that their programme required documentation of reasons for time‐off requests. Previous studies suggest that residents are less likely to access health care (physical or mental) because of concerns over confidentiality and privacy 23,24 . Thus, any requirement that residents document why they are requesting time off is likely to deter them from addressing important needs such as mental health appointments.…”
Section: Discussionmentioning
confidence: 99%
“…17 Data regarding residents postponing or avoiding care remain scarce. 18,19 We examined the attitudes and behaviors of residents in primary care and specialty programs at one institution pertaining to their own health care. In this report, we focused on items related to postponing or avoiding care.…”
Section: Roughly100000physiciansengageinmentioning
confidence: 99%
“…These findings are consistent with a British study that reported that most junior doctors had not taken any leave for the majority of illness episodes during the prior 6 months and that a majority of them had expressed concerns about colleagues having to cover. 19 Residents were asked whether colleagues who must miss work because of health issues were treated with empathy or ostracism. They endorsed both.…”
Section: Residents' Perspectives On Personal Health Needs and Care-sementioning
confidence: 99%
“…It also indicates that they resist being on sick leave Forsythe et al, 1999) and that they tend to work when sick (Baldwin et al, 1997;Kivimäki et al, 2001;Cupples, Bradley, Sibbett & Thompson, 2002;Tillett, 2003), unlike other categories with high income and similar status (McKevitt, Morgan, Dundas, Holland, 1997), but like other categories within the health care sector (Aronsson, Gustafsson & Dallner, 2000). Previous research shows that this is the result of perceived pressure to be at work (Töyry et al, 2000;Aronsson et al, 2000;Thompson et al, 2001;Kivimäki et al, 2001;Perkin, Higton & Witcomb, 2003) and that members of professional categories that are not easily replaced by others when absent show a higher degree of sick presence than others (Aronsson et al, 2000).…”
Section: Introductionmentioning
confidence: 81%